PENGARUH AKTIVITAS BELAJAR DI LUAR JAM SEKOLAH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI DAN BUDI PEKERTI KELAS XI IPA DI SMAN 2 KUANTAN MUDIK TP. 2021/2022 - Rovi Mufita Indriani; Zulhaini Zulhaini; A. Mualif (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
The success of students in achieving educational goals can be seen through learning outcomes by maximizing learning activities outside school hours. Because these activities can affect student learning outcomes. At SMAN 2 Kuantan Mudik, symptoms were found that grade XI science students: (1) Repeating lessons at home, (2) Doing assignments or homework, and (3) Reading books or other reading materials as an additional source of learning material. However, 46.6% of them have problems with learning outcomes by not reaching the KKM limit in PAI and Budi Pekerti subjects. Based on this background, this study aims to determine whether there is an effect of learning activities outside of school hours on the learning outcomes of PAI and Budi Pekerti students of class XI IPA at SMAN 2 Kuantan Mudik. This research is a causal associative quantitative type with a sample of 30 people. The primary data collection techniques used are questionnaires and documentation. While the data analysis technique used is Simple Linear Regression. The results showed that there was no effect of learning activities outside of school hours on student learning outcomes because the t-test showed that the t-test equation was 1.375 which was smaller than the t-table value of 2.048. Likewise in the Significance Test where the value (Sig.) 0.180 is greater than the probability of 0.05.